TANNING IN BODY DYSMORPHIC DISORDER - Phillips, Katharine A. (2006)
Tanning in body dysmorphic disorder (BDD) has not previously been studied. In this study, 200 subjects with BDD were evaluated with measures to examine the prevalence of BDD-related tanning—i.e., darkening one's skin color by direct exposure to sunlight or artificial light which is motivated by a desire to improve a perceived appearance defect (i.e., a BDD concern). We also examined clinical characteristics of individuals who engaged in BDD-related tanning. 25% (95% CI, 19.0%–31.0%) of subjects reported BDD-related tanning. Among tanners, the skin was the most common body area of concern (84.0%). All tanners experienced functional impairment due to BDD, 26% had attempted suicide, and quality of life was markedly poor. 52% of tanners had received dermatologic treatment, which was usually ineffective for BDD symptoms. Tanners were more likely than non-tanners to compulsively pick their skin. In conclusion, tanning—a behavior with well-known health risks—is a relatively frequent BDD-related behavior.